The role of Indian gynecologists in oncofertility care and counselling - Nalini Mahajan; Madhuri Patil; Surleen Kaur; Simrandeep Kaur; Padmaja Naidu (Wolters Kluwer Medknow Publications, 2016)
Oncofertility is gaining importance because of increasing cancer incidence, high survivorship, the need to provide a good quality of life to survivors and the desire of patients to preserve their fertility. Disseminating information about the effect of cancer and cancer treatment on fertility and the availability and effectiveness of fertility preservation techniques is critical. Gynaecologists in India act as family physicians and are in a unique position to guide cancer patients on issues of fertility and fertility preservation. Their contribution in oncofertility is vital to improve the quality of life of many young survivors. This paper presents the result of a survey done with Indian gynaecologists. The aim of this survey was to ascertain awareness and knowledge of reproductive damage by cancer therapy, knowledge of fertility preservation techniques and an understanding of the barriers to fertility preservation. This information would assist in planning programs to improve oncofertility care and counselling.